Evaluating prevalence of mesiodense in 6-9 years children of Tehran - J. Mahmodian; A. Kosari; Gh. Mighani (Tehran University of Medical Sciences, 1993)
Mesiodense have drawn attention of many researchers. According to the available data, there has not been any study on this issue in our country and due to racial variation in Iran, it is essential to evaluate the prevalence of mesiodense in our country. This article has evaluated this on 6-9 years students of Tehran. Complete evaluation is needed according to the lesions that mesiodense can bring about as well as prevention and treatment of this disorder and clinical care following diagnosis. Among 2686 randomly selected students ( 1128f/1559m) , 38 cases in boys and 5 case in girls were found. Therefore, the incidence rate was 5.5 times more in boys which is higher than the other published data. Prevalence of supernumerary teeth was 1.6% of which 88.3% were impacted and only 5.34% were located inversely. In Most cases(93%), single supernumerary teeth were founded.